Derivational Process of Wawonii Language - Yuliyanah Sain; Andi Rachmawati Syarif (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
This research focused on derivational process in Wawonii language at Wawonii regency. The main objective of this research was to find out derivational process of affixation in Wawonii language. This research used qualitative analysis, the data sources in this research are oral data and written data by applying some techniques of collecting data as follows: record, note taking, translation, and introspection. After the data collected the writer analyzed them through the following steps namely: making the table of the gathered data that indicate the derivational affixation in Wawonii language, the table of derivational process, making formulation and following by examples. The result of this research show that Wawonii language has derivational process of affixation consists of four affixation namely: prefix consist of four prefixes namely mon-, me-, po-, mong-, suffix consist of three suffixes namely  -no, -omo, -io, confix consist of three confixes namely   mo-i, pe-no, and infix consist of one infix namely  -in-.